2001
DOI: 10.1126/science.1062872
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI Investigation of Emotional Engagement in Moral Judgment

Abstract: The long-standing rationalist tradition in moral psychology emphasizes the role of reason in moral judgment. A more recent trend places increased emphasis on emotion. Although both reason and emotion are likely to play important roles in moral judgment, relatively little is known about their neural correlates, the nature of their interaction, and the factors that modulate their respective behavioral influences in the context of moral judgment. In two functional magnetic resonance imaging (fMRI) studies using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

168
3,587
23
134

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,637 publications
(3,912 citation statements)
references
References 9 publications
168
3,587
23
134
Order By: Relevance
“…One recent study on logical reasoning demonstrated activation in VMPFC when the logical response was overcome by belief bias (i.e., when subjects responded on the basis of personal beliefs rather than the logic of the situation) (Goel and Dolan, 2003). A study involving moral personal, moral impersonal, and nonmoral judgments has shown greater activation of MPFC in the moral personal condition compared to the other conditions (Greene et al, 2001). 3 Our results are also consistent with neuroanatomical evidence.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…One recent study on logical reasoning demonstrated activation in VMPFC when the logical response was overcome by belief bias (i.e., when subjects responded on the basis of personal beliefs rather than the logic of the situation) (Goel and Dolan, 2003). A study involving moral personal, moral impersonal, and nonmoral judgments has shown greater activation of MPFC in the moral personal condition compared to the other conditions (Greene et al, 2001). 3 Our results are also consistent with neuroanatomical evidence.…”
Section: Discussionsupporting
confidence: 86%
“…One possible basis for this connection is an interaction between L/DLPFC and VMPFC during reasoning. While several neuroimaging and patient studies have shown a dissociation between L/DLPFC and VMPFC in cognitive and affective processing (Goel and Dolan, 2001a;Greene et al, 2001;Hariri et al, 2000;Koechlin et al, 2000;Stuss and Levine, 2002), a predicted interaction be-tween L/DLPFC and VMPFC in reasoning tasks, as a function of emotional saliency, remains to be demonstrated.…”
Section: Introductionmentioning
confidence: 98%
“…For example, based on our low-level non-conceptual feelings about a certain action event we might modify our normative judgments, e.g. when being personally involved we might come to a normative judgment that is mainly carried by emotional involvement, but not by rational argument (Greene & Haidt, 2002;Greene, Sommerville, Nystrom, Darley, & Cohen, 2001); or when lacking the capacity of emotionally assessing an action effect (e.g. due to a brain disease), we are impaired in forming out moral judgments (Damasio, 2003).…”
Section: General Characteristicsmentioning
confidence: 99%
“…In the human brain, these areas include the posterior cingulate cortex, retrosplenial cortex, lateral parietal cortex, medial prefrontal cortex, superior frontal gyrus, inferior temporal gyrus, parahippocampal gyrus, and the cerebellar tonsils (Fox et al, 2005). In humans, heightened default system activity has been linked to complex cognitive processes, such as theory of mind (Saxe and Kanwisher, 2003), moral reasoning (Greene et al, 2001), active self-referential behavior (Vogeley and Fink, 2003), recollection (Wagner et al, 2005) and imagining the future (Addis et al, 2007). Recently, Vincent and colleagues (2007) demonstrated with fMRI that many elements of this default system are present in the anesthetized macaque monkey brain.…”
Section: Neonatal Amygdala Lesions and Resting Brain Metabolismmentioning
confidence: 99%